An Outpatient, Dose-Intense, Intravenous Cisplatin and Oral Etoposide Regimen for the Treatment of Advanced, Platinum-Resistant Ovarian Cancer. Issue 3 (1st March 2018) - Morgan, Robert D.; Clamp, Andrew R.; Hasan, Jurjees; Mitchell, Claire; Saunders, Geoff; Mescallado, Nerissa; Welch, Richard; Jayson, Gordon C.
Abstract : Objectives: Advanced-stage, platinum-resistant, ovarian cancer can be treated with dose-intense chemotherapy; one such regimen includes intravenous cisplatin and oral etoposide. To minimize the toxicity associated with weekly cisplatin, pretreatment and posttreatment hydration is required, often necessitating inpatient, overnight admission. We report a shorter, within-day regimen for delivering weekly cisplatin. Methods: This was a retrospective study to assess the use of standard (inpatient; treatment time of 12 hours) versus modified (outpatient; treatment time of 4 hours) regimens. The primary outcome included all-grade and grade 3/4 adverse events. Secondary outcomes included clinical benefit response and, median progression-free survival and overall survival. Results: Between January 2012 and December 2014, 66 women with metastatic ovarian cancer received dose-intense weekly cisplatin and oral etoposide (n = 45 standard, n = 21 modified). The commonest all-grade adverse events were anemia (96% vs 90%, standard and modified, respectively), fatigue (73% vs 67%), neutropenia (71% vs 76%), hypocalcemia (51% vs 43%), and thrombocytopenia (49% vs 57%). There were no statistically significant differences in the incidence or grades of adverse events. The clinical benefit response was 53% in the standard group and 62% in the modified group ( P = 0.9). The median progression-free survival was 4.2 and 6.5 months (incidence rate ratio, 1.22; 95% confidence interval, 0.71–2.15; P = 0.29), and median overall survival was 6.6 and 8.4 months (incidence rate ratio, 1.83; 95% confidence interval, 1.04–3.35; P = 0.03), in favor of the modified regimen. Conclusions: Our shorter, within-day regimen for delivering dose-intense weekly cisplatin and oral etoposide to treat platinum-resistant metastatic ovarian cancer is safe and efficacious.